2020
DOI: 10.1073/pnas.1917421117
|View full text |Cite
|
Sign up to set email alerts
|

Localization of sterols and oxysterols in mouse brain reveals distinct spatial cholesterol metabolism

Abstract: Dysregulated cholesterol metabolism is implicated in a number of neurological disorders. Many sterols, including cholesterol and its precursors and metabolites, are biologically active and important for proper brain function. However, spatial cholesterol metabolism in brain and the resulting sterol distributions are poorly defined. To better understand cholesterol metabolism in situ across the complex functional regions of brain, we have developed on-tissue enzyme-assisted derivatization in combination with mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 78 publications
3
79
0
1
Order By: Relevance
“…S2B). These observations also agree with a recent study indicating a low level of 24S-hydroxycholesterol in the cerebellum 33 , while an earlier immunohistochemistry study detected a relatively high level of CH24H expression in Purkinje cells 34 . To further characterize the CH24H binding specificity of soticlestat, biodistribution experiments were conducted in vivo, comparing CH24H-KO and WT mice following intravenous injection (Fig.…”
Section: Ch24h Inhibitory Activity and In Vitro/in Vivo Target Engagesupporting
confidence: 93%
“…S2B). These observations also agree with a recent study indicating a low level of 24S-hydroxycholesterol in the cerebellum 33 , while an earlier immunohistochemistry study detected a relatively high level of CH24H expression in Purkinje cells 34 . To further characterize the CH24H binding specificity of soticlestat, biodistribution experiments were conducted in vivo, comparing CH24H-KO and WT mice following intravenous injection (Fig.…”
Section: Ch24h Inhibitory Activity and In Vitro/in Vivo Target Engagesupporting
confidence: 93%
“…Theofilopoulos et al suggested that the loss of motor function in two diseases resulting from inborn errors of metabolism, cerebrotendinous xanthomatosis (deficiency in CYP27A1) and hereditary spastic paresis type 5 (deficiency in CYP7B1) is a consequence of a reduced production of 3β,7α-diHCA in cerebrotendinous xanthomatosis, with the additional over production of neurotoxic 3β-HCA in spastic paresis type 5 providing a double-hit mechanism in the latter disease (see Figure 4 for CYP catalysed reactions) (Theofilopoulos et al, 2014). Interestingly, 3β,7α-diHCA is found to be most abundant in mouse cerebellum (Yutuc et al, 2020) Table S1 cholestenoic acids, (25R)26-hydroxycholesterol ((25R)26-HC, also called by the non-systematic name 27-hydroxycholesterol, 27-HC, note if stereochemistry at C-25 is not defined it is assumed to be 25R), a weak liver X receptor agonist (Fu et al, 2001), also accumulates in CSF of spastic paresis type 5 patients (Schols et al, 2017;Theofilopoulos et al, 2014) and Hauser et al have suggested that neurotoxic effects of (25R)26-HC are major contributors to the spastic paresis type 5 phenotype (Hauser et al, 2019). It is noteworthy that neither Cyp27a1 −/− or Cyp7b1 −/− mice shows a motor neuron phenotype.…”
Section: Liver X Receptorsmentioning
confidence: 99%
“…There is good evidence for the production of 7α,(25R)26-diHC in the brain from either imported or in situ synthesised (25R)26-HC (Heverin et al, 2005;Iuliano et al, 2015;Yutuc et al, 2020 (Soroosh et al, 2014). In primary cells, both oxysterols were found to enhance the differentiation of IL-17-producing cells in a RORγt-dependent manner and Th17 cells were found to produce both oxysterols (Soroosh et al, 2014).…”
Section: Retinoic Acid Receptor-related Orphan Receptorsmentioning
confidence: 99%
See 2 more Smart Citations